Language of Instruction for Teaching Mathematics at Primary Level: Controversy in Pakistan - Saira Maqbool, Mamoona Ghani, Saima Maqbool (PJE, 2023)
One of the factors credited to the poor performance of students in Pakistan is the medium of instruction used at primary level. More than 70 languages are alive languages/spoken languages of Pakistan and its government is confused which language to select as MOI (medium of instruction) at primary level, i.e. Urdu which is the national language of Pakistan. This paper explores the MOI controversy in Pakistan it also sought to explore the possibilities and effectiveness of using English versus Urdu as a medium of instruction for the teaching of Mathematics in primary schools in Pakistan. A teaching experiment was conducted to compare the use of English as a medium of instruction with Urdu as medium of instruction in the teaching and learning of Mathematics to grade 3 class. t-test was applied to find of the difference of the progress between two groups, one group taught in Urdu as MOI and second in English as MOI. Major findings of the research indicated that the use of Urdu as a medium of instruction in the teaching of Mathematics to primary school students had a more positive impact upon the teaching of Mathematics. This discussion contains language controversy from the pre-partition time (1835-1947) till date in different political regimes to understand the causes of disagreement upon the selection of a single MOI in education. Applicable recommendations were made in the light of the findings